Visual imagery influences brain responses to visual stimulation in bilateral cortical blindness. (November 2015) - de Gelder, Beatrice; Tamietto, Marco; Pegna, Alan J.; Van den Stock, Jan
Abstract: Mental imagery is a powerful mechanism that may facilitate visual perception as well as compensate for it. The role of V1 in mental imagery is still a matter of debate. Our goal here was to investigate whether visual imagery was still possible in case of bilateral V1 destruction behaviorally evidenced by total clinical blindness and if so, whether it might boost residual visual perception. In a factorial fMRI design, faces, scenes or scrambled images were presented while a rare patient with cortical blindness over the whole visual field due to bilateral V1-lesions (TN) was instructed to imagine either an angry person or a neutral object (tree). The results show that visual imagery of a person activates frontal, parietal and occipital brain regions similar to control subjects and hence suggest that V1 is not necessary for visual imagery. In addition, the combination of visual stimulation and visual imagery of socio-emotional stimuli triggers activation in superior parietal lobule (SPL) and ventromedial (vmPFC) and dorsolateral prefrontal cortex (DLPFC). Finally, activation during residual vision, visual imagery and their interaction overlapped in the SPL, arguing for a central role of feeling in V1-independent vision and imagery.